(untitled) (Global Journal of Management and Business Research, 1970)
Over the past three decades female entrepreneurship has become increasingly important in most industrialized countries but also in developing countries The objective of this article is to highlight the exogenous factors of the financial performance of women entrepreneurs in order to promote the emergence of female entrepreneurship in Cameroon To achieve our objective we relied on a mixed approach qualitative and quantitative The qualitative approach allowed us to better define the concept of performance To this end an interview guide was administered to 10 women entrepreneurs and the saturation sampling method enabled us to achieve our objectives Regarding the quantitative approach a questionnaire was administered to 300 women but only 250 responded We used the LOGIT to assess the impact of the factors selected Our results reveal that socio-cultural factors influence of family religion and ethnicity and the access to financing factor guarantee business plan are the main explanatory factors of financial performance It would therefore be wise to undertake legislative and administrative reforms with a view to fully ensure gender equality in access to economic resources right to inheritance and land ownership access to credit training and information